Production of Organic Acid and Short-Chain Fatty Acids (SCFA) from Lactic Acid Bacteria Isolate on Oligosaccharide Media - Yati Maryati; Lilis Nuraida; Ratih Dewanti Hariyadi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
The growth of microorganisms in food, one of which is lactic acid bacteria (LAB), can produce metabolites beneficial to health. It is essential to study the results of LAB metabolism to improve the quality of a functional food product. This study aimed to evaluate the isolates Lactobacillus acidophilus FNCC 0051 and Lactobacillus rhamnosus R23 to metabolize oligosaccharides as a carbon source so that the final fermentation product can benefit health especially in lowering cholesterol. In vitro testing was carried out on MRS media with or without oligosaccharides, either singly or in a combination consisting of galactooligosaccharides (GOS), fructooligosaccharides (FOS), inulin (IN), inulin hydrolyzate (HI), or their combination as prebiotics by adding 0.3 % oxbile (bile salt) and inoculated with 1% v/v LAB isolate culture and incubated at 37°C for 24 hours. The results showed that the main product of oligosaccharide metabolism by L. acidophilus FNCC 0051 and L. rhamnosus R23 produced several organic acids (lactic acid), including short-chain fatty acids (SCFA) (acetic acid, propionic acid, and butyric acid). The single and combined carbon sources affected the proportion of lactic acid and acetic acid produced by L. acidophilus FNCC0051 (p<0.05). However, they did not affect the proportions of propionic acid and butyric acid. While in L. rhamnosus R23 (p<0.05), the presence of a single carbon source significantly affected the proportions of lactic acid, acetic acid, propionic acid, and butyric acid, while the combination of oligosaccharides affected the proportions of lactic acid and butyric acid produced. SCFA is the main product of prebiotic metabolism, but the characteristics of the acid produced have not been identified. The fermentation pattern is thought to be related to molecular weight, chain length, and oligosaccharide structure. Short-chain molecules, such as FOS generally ferment more rapidly than long-chain molecules such as inulin. The results of this study indicate that both isolates can be used as probiotics in the development of symbiotic products with the addition of oligosaccharides, which have a physiological effect in lowering cholesterol levels.